2022
DOI: 10.1021/acs.jnatprod.1c01114
|View full text |Cite
|
Sign up to set email alerts
|

Syzysamalactone, an Unusual 11-Carbon δ-Lactone Derivative from the Fresh Ripe Fruits of Syzygium samarangense (Wax Apple)

Abstract: To study the chemical constituents from the ripe fresh fruits of Syzygium samarangense (wax apple) and their potential health effects, a phytochemical investigation was undertaken. A new δ-lactone derivative, syzysamalactone (1), along with a known biogenetically related δ-lactone derivative, 6-pentyl-α-pyrone (2), were isolated from the fresh ripe fruits of S. samarangense. Syzysamalactone (1) is an unusual 11-carbon δ-lactone derivative, and its chemical structure and absolute configuration were elucidated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The chemistry of apple peel is very complex and has been adapted for its biological function. The peel's outer surface consists of cuticle waxes composed of fatty alcohol, fatty acids and long chain hydrocarbons [45][46][47]. Additionally, there are different class of compounds such as flavonoids [48,49], phenolic acids [50,51], triterpene esters [52] and proanthocyanidins [53].…”
Section: Discussionmentioning
confidence: 99%
“…The chemistry of apple peel is very complex and has been adapted for its biological function. The peel's outer surface consists of cuticle waxes composed of fatty alcohol, fatty acids and long chain hydrocarbons [45][46][47]. Additionally, there are different class of compounds such as flavonoids [48,49], phenolic acids [50,51], triterpene esters [52] and proanthocyanidins [53].…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary experimental results revealed that the 85% ethanol extract of the stems and leaves of C. cochinchinense showed notable inhibitory effect against nitric oxide (NO) production induced by lipopolysaccharide in mouse macrophage RAW 264.7 cells with an IC 50 value of 9.68 ± 0.12 μg/mL in vitro, as well as anti-HIV-1 reverse transcriptase (RT) effect with an EC 50 value of 7.19 μg/mL. To fully explore the enormous potential of Hainan’s unique tropical medicinal plants and tropical fruits in the prevention and treatment of major human diseases, in the course of our continuing investigation of biologically active and structurally diverse natural products from the tropical medicinal plants and tropical fruits [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], a phytochemical study on the stems and leaves of C. cochinchinense was thus undertaken and led to the isolation and characterization of four new xanthones, cratocochinones A–D ( 1 – 4 ),which are a kind of rare natural product with extensive biological activities [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], alongside eight known analogues 5 – 12 . Their chemical structures were determined on the basis of comprehensive spectral analyses.…”
Section: Introductionmentioning
confidence: 99%